Frontiers of quantitative economics - Intriligator, Michael D.; Kendrick, David A.; Econometric Society (Amsterdam : North-Holland, 1974)
The series consists of a number of unpublished studies, which the editors believe represent fresh contributions to economic science. The studies covers both the activities of the theoretical economist and the research worker. Business cycle research and national accounting, research work on behalf of economic policy, and problems of planning are the main sources of the subjects dealt with. It is hoped that these studies will help to stimulate the exchange of scientific information and to reinforce international cooperation in the field of economics.
Volume 2.
"Papers invited for presentation at the Econometrics Society Winter Meetings, Toronto, 1972."
Includes bibliographical references and index.
rpm 13/07/2017
Loans
Keywords: Econometrics; Economics, Mathematical; Mathematical economics; Economics -- Mathematical models